Wideband power amplifier based on Wilkinson power divider for s-band satellite communications - Mabrok, Mussa; Zakaria, Zahriladha; Sutikno, Tole; Alhegazi, Ammar (Bulletin of Electrical Engineering and Informatics, 2019)
This paper presents design and simulation of wideband power amplifier based on multi-section Wilkinson power divider. Class-A topology and ATF-511P8 transistor have been used. Advanced Design System (ADS) software used to simulate the designed power amplifier. The simulation results show an input return loss (S11)<-10dB, gain (S21)>10 dB over the entire bandwidth, and an output power around 28dBm at the Centre frequency of 3GHz. The designed amplifier is stable over the entire bandwidth (K>1). Inter-modulation distortion is -65.187dBc which is less than -50dBc. The designed amplifier can be used for the microwave applications which include weather radar, satellite communication, wireless networking, mobile, and TV.